Single-crystal gradient plasticity with an accumulated plastic slip: Theory and applications - Bayerschen, Eric (Schriftenreihe Kontinuumsmechanik im Maschinenbau / Karlsruher Institut für Technologie, Institut für Technische Mechanik - Bereich Kontinuumsmechanik, 2017)
In experiments on metallic microwires, size effects occur as a result of the interaction of dislocations with, e.g., grain boundaries. In continuum theories this behavior can be approximated using gradient plasticity. A numerically efficient geometrically linear gradient plasticity theory is developed considering the grain boundaries and implemented with finite elements. Simulations are performed for several metals in comparison to experiments and discrete dislocation dynamics simulations.